2007
DOI: 10.2478/v10035-007-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Total Thyroidectomy on Orbital Opthalmopathy and Levels of Antithyroid Antibodies in Patients with Graves' Disease

Abstract: 3Kierownik: prof. dr hab. M. ZabelGraves' disease is an autoimmune disease. One of the most severe complications of Graves' disease is orbitopathy. The aim of the study was to estimate the influence of total thyroidectomy on the postoperative course of exophthalmus and determine the levels of thyroid antibodies after surgery. Material and methods. During the period between 2002 and 2005, 1514 strumectomies were performed at the I Chair and Department of General, Gastroenterological and Endocrine Surgery, Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…However, a comparison of two different surgical approaches (total thyroidectomy vs. subtotal thyroidectomy) for patients with moderate-tosevere GO showed that the eye disease improved during 3 years of follow-up in all patients (546). In another series of 42 patients with progressive GO treated with total thyroidectomy, exophthalmos was stable in 60% of cases and improved in the remainder (547), suggesting that surgery is not detrimental to GO and may be associated with improvement in some patients. Additionally, a more recent study suggests that surgery might lead to a more rapid improvement in GO than ATDs, and it might thus be a better option for patients that are most concerned about GO changes (548).…”
Section: And Recommendation 103mentioning
confidence: 99%
“…However, a comparison of two different surgical approaches (total thyroidectomy vs. subtotal thyroidectomy) for patients with moderate-tosevere GO showed that the eye disease improved during 3 years of follow-up in all patients (546). In another series of 42 patients with progressive GO treated with total thyroidectomy, exophthalmos was stable in 60% of cases and improved in the remainder (547), suggesting that surgery is not detrimental to GO and may be associated with improvement in some patients. Additionally, a more recent study suggests that surgery might lead to a more rapid improvement in GO than ATDs, and it might thus be a better option for patients that are most concerned about GO changes (548).…”
Section: And Recommendation 103mentioning
confidence: 99%
“…However, a comparison of two different surgical approaches (total thyroidectomy vs. subtotal thyroidectomy) for patients with moderate-to-severe GO showed that the eye disease improved over 3 years of follow-up in all patients (330). In another series of 42 patients with progressive GO treated with total thyroidectomy, exophthalmos was stable in 60% of cases and improved in the remainder (331), suggesting that surgery is not detrimental to GO and may be associated with improvement in some patients. Other studies suggest that ATDs may not adversely impact mild active GO, but do not address severe GO (318).…”
Section: And Recommendation 85mentioning
confidence: 99%
“…Similarly, in the present study they accounted for just 3.5% of all patients, but there were no cases of permanent HPT in this subgroup. There are some literature reports that claim thyroid surgery does not carry a high risk of complications in Graves’ disease, including patients with high titers of the anti-TSH receptor antibodies [ 25 ]. Hallgrimsson et al found that the differences in the incidence of hypocalcemia following total thyroidectomy for Graves’ disease and for nontoxic multinodular goiter were not statistically significant [ 21 ].…”
Section: Discussionmentioning
confidence: 99%